Laboratories of faith : mesmerism, spiritism, and occultism in modern France - Monroe, John Warne, 1973- (Cornell University Press, 2008)
"In an evocative history of alternative religious practices in France in the second half of the nineteenth and beginning of the twentieth centuries, John Warne Monroe tells the interconnected stories of three movements - Mesmerism, Spiritism, and Occultism. Adherents of these groups, Monroe reveals, attempted to "modernize" faith by providing empirical support for metaphysical concepts. Instead of trusting theological speculation about the nature of the soul, these believers attempted to gather tangible evidence through Mesmeric experiments, seances, and ceremonial magic." "Featuring eerie spirit photographs, amusing Daumier lithographs, and a posthumous autograph from Voltaire, as well as extensive documentary evidence, Laboratories of Faith gives readers a sense of what being in a seance or a secret-society ritual might actually have felt like and why these feelings attracted participants. While they never achieved the transformation of human consciousness for which they strove, these thinkers and believers nevertheless pioneered a way of "being religious" that has become an enduring part of the Western cultural vocabulary."--Jacket